THE QUEST FOR DISCOVERING EXTRAGALACTIC CEPHEIDS - Szabados, Laszlo (Одеські астрономічні публікації, 2017)
Chronology of studying extragalactic Cepheids is summarized, and the census of known classical Cepheids and their metal-deficient siblings, the anomalous Cepheids is taken. Up to now (August 2005) about 11000 Cepheids have been revealed in 74 galaxies. Cepheids belonging to the Milky Way galaxy only represent about 6 percent of the total Cepheid sample.